Perioperative Complications After Proctectomy for Rectal Cancer: Does Neoadjuvant Regimen Matter?. Issue 2 (February 2022) - Bauer, Philip S.; Chapman, William C.; Atallah, Chady; Makhdoom, Bilal A.; Damle, Aneel; Smith, Radhika K.; Wise, Paul E.; Glasgow, Sean C.; Silviera, Matthew L.; Hunt, Steven R.; Mutch, Matthew G.
Abstract : Objective: Investigate the association between neoadjuvant treatment strategy and perioperative complications in patients undergoing proctectomy for nonmetastatic rectal cancer. Summary of Background Data: Neoadjuvant SC-TNT is an alternative to neoadjuvant CRT for rectal cancer. Some have argued that short-course radiation and extended radiation-to-surgery intervals increase operative difficulty and complication risk. However, the association between SC-TNT and surgical complications has not been previously investigated. Methods: This single-center retrospective cohort study included patients undergoing total mesorectal excision for nonmetastatic rectal cancer after SC-TNT or CRT between 2010 and 2018. Univariate analysis of severe POM and multiple secondary outcomes, including overall POM, intraoperative complications, and resection margins, was performed. Logistic regression of severe POM was also performed. Results: Of 415 included patients, 156 (38%) received SC-TNT and 259 (62%) received CRT. The cohorts were largely similar, though patients with higher tumors (69.9% vs 47.5%, P < 0.0001) or node-positive disease (76.9% vs 62.6%, P = 0.004) were more likely to receive SC-TNT. We found no difference in incidence of severe POM (9.6% SC-TNT vs 12.0% CRT, P = 0.46) or overall POM (39.7% SC-TNT vs 37.5% CRT, P = 0.64) between cohorts. Neoadjuvant regimen was also not associated with a difference in severe POM (odds ratio 0.42, 95% confidence interval 0.04–4.70, P = 0.48) in multivariate analysis. There was no significant association between neoadjuvant regimen and any secondary outcome. Conclusion: In rectal cancer patients treated with SC-TNT and proctectomy, we found no significant association with POM compared to patients undergoing CRT. SC-TNT does not significantly increase the risk of POM compared to CRT. Abstract : Supplemental Digital Content is available in the text